Analisis Implementasi Prosedur Keselamatan Distribusi BBM: Studi Kasus PT Pertamina Patra Niaga Fuel Terminal Jambi - Afrianti, Tiara Sebrina; Ananda, Hafiz Adli; Ihsan, Taufiq (National Journal of Occupational Health and Safety, 2025)
Distribution of fuel oil (FO) using tanker trucks is highly risky. Although PT Pertamina Patra Niaga has adopted the Tanker Truck Safety Management System, accidents still occur. This study aimed to evaluate the implementation of FO distribution safety procedures at PT Pertamina Patra Niaga Fuel Terminal Jambi. This study used a cross-sectional approach. Primary data were collected through direct observation of 50 tanker trucks, including the physical condition, completeness of documents, and driver behavior. Secondary data, such as accident and inspection reports, were also analyzed. Fishbone analysis was used to identify the root cause, and scoring was done to determine the solution. The evaluation showed that although the company had made efforts to implement safety procedures properly, 79 potential hazards were found in 38 of the 50 tanker trucks observed. The most common findings were related to damage to the emergency cut-off, fire extinguishers, and tires. Fishbone analysis identified human factors (awareness and understanding), materials (equipment quality), methods (inspection procedures), and the environment (road conditions) as the causes. The fuel distribution safety procedure at PT Pertamina Patra Niaga Fuel Terminal Jambi is quite effective, but it needs improvement in supervision, training, and technology utilization. Further research with broader samples and coverage areas is recommended. Keywords: fishbone analysis, occupational safety, tanker trucks, fuel terminal.